2011
DOI: 10.1016/j.febslet.2011.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Variable responses of small and large human hepatocytes to hypoxia and hypoxia/reoxygenation (H-R)

Abstract: Hypoxia and hypoxia–reoxygenation (H–R) regulate human hepatocyte cell death by mediating the accumulation of reactive oxygen species (ROS). Hepatocytes within the liver are organised into peri-portal (PP) and peri-venous (PV) subpopulations. PP and PV hepatocytes differ in size and function. We investigated whether PP and PV human hepatocytes exhibit differential susceptibility to hypoxic stress. Isolated hepatocytes were used in an in vitro model of hypoxia and H–R. ROS production and cell death were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Hypoxia-induced cell death is a major concern in various clinical settings and plays a critical role in various physiopathological processes, such as hypoxic/ischemic disease, organ transplantation, angiogenesis or tumor invasion ( 33 35 ). I/R injury comprises a series of events that may occur together or separately: Reperfusion arrhythmias, myocardial stunning in ‘reversible mechanical dysfunction’, microvascular damage and cell death ( 36 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia-induced cell death is a major concern in various clinical settings and plays a critical role in various physiopathological processes, such as hypoxic/ischemic disease, organ transplantation, angiogenesis or tumor invasion ( 33 35 ). I/R injury comprises a series of events that may occur together or separately: Reperfusion arrhythmias, myocardial stunning in ‘reversible mechanical dysfunction’, microvascular damage and cell death ( 36 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…These changes cause local hypoxia, which may have an effect on PDLCs and cause release of chemical mediators, resulting in adaptive responses to maintain homoeostasis of periodontal tissue. Hypoxia-induced cell death is a major concern in various clinical settings such as hypoxic/ischaemic disease, organ transplantation, and others (21,(30)(31)(32). To elucidate the mechanisms by which human PDLCs respond to hypoxia, we used treating them with CoCl 2 as a model, and demonstrated that CoCl 2 triggered both apoptosis and autophagy in PDLCs involving the HIF-1a pathway.…”
Section: Discussionmentioning
confidence: 99%
“…16 Here we demonstrate that large/PV hepatocytes ( Fig. 10) increase autophagy significantly more than PP/small human hepatocytes during H-R (Fig.…”
Section: Resultsmentioning
confidence: 90%